Rāhnamā-yi taṣḥīḥ-i mutūn - Jahānbakhsh, Jūyā (Miras Maktoob, ISBN: 9789004365452., 2019)
To know a culture, is to know its written tradition. Before the coming of the printing press, books were transmitted in manuscript form. When texts started to get printed rather than copied, earlier works that until then had only existed in manuscript, came to be printed too. Until the early nineteenth century, a fair copy of a handwritten text would be all that was needed to turn an older work into a printed book. Today, all this has changed and most ancient texts are now published on the basis of a commonly accepted methodology. In the Islamic world, where we have thousands of works in manuscript that still await a proper edition, these modern methods are not always accessible to local scholars and uncritical editions still abound. This Persian guide to the publication of manuscripts is meant to change that situation. As such, it is an important statement on the advances in scholarship in Iran.